Analysis of Factors Affecting Credit Distribution for Commercial Banks in Central Kalimantan Province (Case Study of Central Kalimantan Regional Development Banks - Lirayanti Sihotang (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2020)
The purpose of this study was to determine the effect of third party fund (DPK), capital adequacy ratio (CAR), non performing loan (NPL) on credit interest rate on credit distribution at the Regional Development Bank of Central Kalimantan. This study uses the Central Kalimantan Regional Development Bank as the object of research, with a research period from 2012-2020. The data used in this study were obtained from the annual report of the Central Kalimantan Regional Development Bank from 2012-2020. The analytical technique used is multiple linear regression analysis using the SPSS 21 analysis tool. Based on the results of the study that the third party fund (DPK) variable has a positive and significant effect on Loan Distribution of the Regional Development Bank of Central Kalimantan, the capital adequacy ratio (CAR) has a positive and no positive effect. Significantly to the distribution of loans to the Regional Development Bank of Central Kalimantan, non performing loans (NPL) and the interest rate of credit have a negative and significant effect on the distribution of loans to the Regional Development Bank of Central Kalimantan